Expression of facilitative glucose transport proteins during development of squamous cell carcinomas of the head and neck - Reisser, Christoph; Herold-Mende, Christel; Bannasch, Peter (International journal of cancer, 1999)
Positron emission tomography studies on malignant head and neck tumors have shown that tumor growth and elevated glucose uptake are associated. On a molecular level, glucose uptake is mediated by specific glucose transport proteins, which exhibit an altered expression in head and neck malignant neoplasms. However, it is unknown when during development of squamous cell carcinomas an alteration of the expression of glucose transport proteins occurs. We have studied the expression of different facilitating glucose transport proteins (GLUT 1, 2, 3 and 4) by immunohistochemistry in a variety of preneoplastic and neoplastic mucosal lesions of the head and neck. We have observed weak expression of GLUT 1 in normal mucosa, a marked expression of GLUT 1 throughout preneoplastic lesions, which correlated well with the degree of dysplasia. In squamous cell carcinomas of the head and neck (HNSCC) and metastases, GLUT 1 was always expressed strongly. In contrast, GLUT 2, 3 and 4 were not detected in any of the epithelial tissues examined. The increased expression of GLUT 1 in dysplastic lesions and its sustained expression in SCC indicate that changes of GLUT 1 expression are early events during development of HNSCC. Therefore, the detection of GLUT 1 might be a reliable marker in the diagnosis of premalignant lesions of the oropharyngeal mucosa.Int. J. Cancer 80:194-198, 1999. © 1999 Wiley-Liss, Inc.
Gesehen am 18.02.2019